Integrated passive filter inductors for motor drive applications - Khowja, Muhammad Raza (2019)
Passive elements such as filter inductors and capacitors occupy a significant amount of space in motor drives and have added penalties of increased system losses and weight. Traditionally, the filters are designed and introduced separately after the drive system components have been defined. This leads to discrete sub-systems which require a functional and structural integration to make efficient and power dense overall system. Such power dense system is the prerequisite in aerospace and marine applications. Therefore, the main focus of this thesis is to look at an integrated approach to design and optimize the filter inductor, both from functional and physical point of integration. Two novel integrative approaches for passive filter inductor are presented in this thesis along with a detailed literature review of passive filters that are being used at present. The first approach is a functional integration of passive filter inductor which uses the inherent motor magnetics to act as a filter inductance instead of introducing a separate filter inductor between the inverter and motor terminals. The mathematical and FE models of the integrated motor have been made using MATLAB®-Simulink and MagNet-Infolytica finite element tool to predict and compare its overall performance with the conventional motor drive system. For the purpose of comparing these two systems, a separate EE core filter inductor is designed and sized using “Area Product” approach. Subsequently, the optimization of the integrated motor is presented in terms of torque ripple, total losses, weight and volume which is then compared with the conventional motor drive. For the purpose of experimental verification, the existing HEMAS motor is modified and tested on a DDS motor drive system. In addition, the concept of motor-shaped inductors are presented which provided an effective structural integration as the inductor can be embedded within the housing of existing motor or generator. The motor-shaped inductors include: motor-shaped rotational inductor and motor-shaped rotor-less inductor. The design procedure of both motor-shaped inductors is explained which is followed by the design optimization process. The design optimization of motor-shaped inductors have been carried out whilst considering various slot-pole combinations and winding configurations which is then compared with the conventional EE core inductor in terms of total losses, weight and AC copper resistance. To validate it experimentally, 12 slots 2 poles rotational inductor is manufactured at The University of Nottingham, UK which is tested on a 49 kW, 20,000 rpm induction motor drive system. The results have been presented at different rotor speeds and supply frequencies. Subsequently, the performance of both rotational inductor and conventional EE core inductor have been compared in terms of synchronous inductance, power losses, DC and AC resistance, power quality, weight and volume.